Reflecting with Schmemann on the Functions of Byzantine Hymnography The Case of the 15 Antiphons during Holy Friday Matins - Lossky-Laham, Olga (2023)
Schmemann’s harsh judgement of the antiphons of Holy Friday matins invites us to consider the role of hymnography in the liturgical celebration. By analysing the historical context of the appearance of the antiphons - according to the methodology proposed by Schmemann - it is possible to consider the way in which these hymns make use of scriptural material by means of patristic intertextuality. The hymns privilege some biblical interpretations in order to encourage the believer to join in the participation in the Kingdom. This parenetic bias, however, often masks the eschatological message contained in the hymns themselves, and even degenerates into denunciatory rhetoric. It is then necessary to recontextualize the functions of hymnography to actualize it, especially by questioning its relationship to Scripture in order to refocus on the theological message.